Menanamkan Nilai-Nilai Islam Melalui Pembiasaan Shalat Berjamaah - Khofi, Mohammad Bilutfikal; Suheri; Miftahus Salam (Fakultas Tarbiyah dan Keguruan dan UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
The inculcation of Islamic values through congregational prayer in madrasas is important in shaping students' religious character. This study aims to identify strategies for instilling Islamic values through congregational prayer in madrasas, including role modelling, reward and punishment, persuasive invitations, and school norms. The research employs a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The findings show that congregational prayer effectively instils values of worship, morality, a spirit of striving, and exemplary behaviour. The role of teachers as role models is crucial in providing examples to students, while the application of rewards and punishments encourages students to be disciplined in their work. Furthermore, persuasive invitations and routine practice through school norms reinforce students' internalization of Islamic values. In conclusion, congregational prayer is an effective method for shaping students' religious character, supported by structured and comprehensive strategies from the madrasa.